Analisis Persepsi Pelaku UMKM terhadap BPJS Ketenagakerjaan Sebagai Upaya Perlindungan Jaminan Sosial: (Studi Kasus Pelaku UMKM Pasar Simpang Limun Medan) - Hidayat, Ryan; Soemitra, Andri; Harahap, Isnaini (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study is to understand and analyze the perception of Micro, Small, and Medium Enterprises in the Simpang Limun Medan Market towards BPJS Employment as a form of social security. This type of research is qualitative descriptive research, where the data must be in the form of descriptive information with theories developed based on the data obtained. This research was carried out at the Simpang Limun Market in Medan. There are 350 MSME actors, the author selected 13 informants of MSME actors to be interviewed. Of these 13 informants, only 4 people are members of BPJS Ketenagakerjaan. Data collection was carried out by observation, documentation, and in-depth interviews.  The data analysis method used in this study is the Miles and Huberman model, which is based on data reduction, namely summarizing, focusing on important aspects, selecting relevant data, and simplifying so that it affects conclusions and verification. The data validity technique is used triangulation by comparing various sources of information. The results of the study show that Micro, Small, and Medium Enterprises in the Simpang Limun Market still have low awareness of BPJS Ketenagakerjaan. Observations in the field show that most MSME actors in Pasar Simpang Limun do not have adequate social security protection, which makes them vulnerable to social and economic risks. Lack of information, cost constraints, and complicated registration procedures are the main factors that hinder their participation in this social security program. In addition, limited access to BPJS offices and negative experiences in filing claims also worsened their perception of the benefits of this program. There needs to be a more effective effort to increase awareness and involvement of MSME actors in BPJS Ketenagakerjaan.